Electrochemical characterization of polylactic acid-block-poly (2-vinylpyridine)/gold nanoparticle composites for glucose biosensor development - Ali, Fathilah; Long, JiaJia; Wan Salim, Wan Wardatul Amani (Kulliyah of Engineering, International Islamic University Malaysia (IIUM), 2017)
Nanocomposites that consist of diblock copolymer (BCP) and gold nanoparticles (AuNPs) can be applied as a matrix to immobilize enzymes or other molecules, based on the well-defined core/shell nanostructures of these composites. In this research, polylactic acid-block-poly(2-vinylpyridine) (PLA-b-P2VP)/hydrogen tetrachloroaurate(III) hydrate (HAuCl4.3H2O) composites were hybridized and then reduced in dichloromethane (DCM) solution. The hybridizations between gold precursors and the P2VP domain were prepared with different ratios of gold to P2VP block (1:1, 1:5, 1:10, 5:1, 10:1) by taking advantage of the association between the longpair nitrogen of the pyridine group of P2VP. The reduction of the Au3+/PLA-b-P2VP composite was accomplished by hydrazine solution in order to get gold nanoparticle/PLA-b-P2VP composites, which was visually confirmed by a direct color change from bright yellow to purple. In this work, ultraviolet–visible (UV-vis) spectroscopy and Fourier transform infrared spectroscopy (FTIR) were used to confirm the association between gold precursors and pyridine groups as well as the synthesis of gold nanoparticles. The composite which labeled as R3 (Au3+: P2VP = 10:1) showed the highest peak current based on the cyclic voltammetry (CV) measurement. Furthermore, graphene oxide (GO) was added into R3 to prepare BCP/AuNPs/GO composite and reduced to BCP/AuNPs/rGO through electrochemical reduction. The resulting BCP/AuNPs/rGO showed high potential to be used in amperometric biosensor